El Monasterio del Santo Sepulcro de Zaragoza en los siglos XIX y XX: The Monastery of the Holy Sepulchre of Zaragoza in the 19th and 20th centuries - Tutor Vicente, Miguel (Artigrama, 2025)
ResumenEl Monasterio del Santo Sepulcro de Zaragoza empeñó un papel estratégico durante los Sitios de Zaragoza (1808-1809). Los bombardeos que sufrió en este conflicto provocaron daños que fueron reparados en la primera mitad del siglo XIX. A finales de dicho siglo, la ruina parcial del convento en la calle Don Teobaldo permitió la ejecución de una nueva fachada hacia la ciudad. A lo largo del siglo XX, tras ser declarado Monumento Nacional, el Estado financió diversas intervenciones en el mismo, como la consolidación de la muralla, la construcción de un nuevo pabellón y la repristinación del claustro.AbstractThe Monastery of the Holy Sepulchre of Zaragoza played a strategic role during the Sieges of Zaragoza (1808-1809). The bombings during this conflict caused damages that were repaired in the first half of the 19th century. At the end of this century, the partial ruin of the convent on Don Teobaldo’s street allowed the construction of a new façade to the city. Throughout the 20th century, after it was declared a National Monument, the State financed various interventions in it, such as the consolidation of the wall, the construction of a new pavilion and the restoration of the cloister.KeywordsMonastery of the Holy Sepulchre of Zaragoza, Sieges of Zaragoza, Ricardo Magdalena Tabuenca, Luis de la Figuera y Lezcano, Manuel Lorente Junquera.